ERROR ANALYSIS ON INDONESIAN YOUTUBE VIDEOS - I GUSTI NGURAH OCTOVA SEVENTILOFA (Universitas Mahasaraswati K. Mataram, 2021)
This study aims to provide education to the wider community in general and to readers or for novice learners of English about errors that often occur or are commonly done by Indonesian YouTubers when speaking English where these YouTubers can be grouped into non-fluent speakers or beginner English learners. The result is that the errors made by these YouTubers can be categorized into four major groups, namely; discourse error, grammatical error, syntactic, and lexical error. The object of his research is limited to videos uploaded to YouTube.com by these YouTubers in a limited number. The methods and approaches used in this research are qualitative methods and objective approaches.